2010
DOI: 10.1063/1.3322895
|View full text |Cite
|
Sign up to set email alerts
|

Oblique electrostatic excitations in a magnetized plasma in the presence of excess superthermal electrons

Abstract: The nonlinear propagation of ion-acoustic waves is considered in a magnetized plasma, composed of kappa distributed electrons and an inertial ion fluid. The fluid-dynamical system of equations governing the dynamics of ion-acoustic waves is reduced to a pseudoenergy-balance equation. The properties of arbitrary amplitude, obliquely propagating ion-acoustic solitary waves are thus investigated via a mechanical-motion analog ͑Sagdeev potential͒ approach. The presence of excess superthermal electrons is shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
87
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(95 citation statements)
references
References 43 publications
8
87
0
Order By: Relevance
“…It has been shown that pair-ion plasmas with positively charged dusts support DIA solitons only of the rarefactive type. There are, however, a number of recent works dealing with the nonlinear properties of solitary waves [12][13][14][15][16][17][18][19][20][21] , electrostatic ion-cyclotron waves 22 shocks 23 in other plasma environments.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that pair-ion plasmas with positively charged dusts support DIA solitons only of the rarefactive type. There are, however, a number of recent works dealing with the nonlinear properties of solitary waves [12][13][14][15][16][17][18][19][20][21] , electrostatic ion-cyclotron waves 22 shocks 23 in other plasma environments.…”
Section: Introductionmentioning
confidence: 99%
“…However, with more and more empirical data becoming available from space plasma systems, it is realized that in such systems, the particle distribution significantly deviates from the Maxwellian distribution [26][27][28] due to the presence of superthermal particles having high energy tails [29]. These superthermal particles can be described bydistribution rather than Maxwellian [30][31][32][33][34][35][36][37][38]. The Lorentzian (or Kappa) distribution has been widely used for conventional plasmas (not for a dust component).…”
Section: Introductionmentioning
confidence: 99%
“…The parameter determines the high energy power law index (which approaches to Maxwellian distribution for ) [40]. The distribution function was argued to provide a much better fit to existing observations than the Maxwellian [29][30][31][32][33][34][35][36][37][38][39][40][41]. The kappa distribution function applications include; for instance, the interpolation of observations in the Earth's foreshock with 3 < e < 6 [42,43] and the solar wind models with coronal electrons with 2 < e < 6 [42,44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using solar wind data, Vasyliunas first predicted a non-Maxwellian distribution [13]; this distribution, which later came to be known as the ''kappa distribution,'' has been found in many magnetospheric and astrophysical environments. Ion-acoustic shock waves in plasmas consisting of superthermal electrons and positrons have been studied recently by many authors [14][15][16][17][18][19][20]; the effects of electrons and positrons on ion acoustic solitary waves have also been studied [21].…”
Section: Introductionmentioning
confidence: 99%